A multi-echelon inventory management framework for stochastic and fuzzy supply chains - Gumus, Alev Taskin; Guneri, Ali Nat (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
In this paper, for effective multi-echelon Supply chains under stochastic and fuzzy environments, an inventory management framework and deterministic/stochastic-neuro-fuzzy cost models within the context of this framework are structured. Then, a numerical application in a three-echelon tree-structure chain is presented to show the applicability and performance of proposed framework. It can be said that, by our framework, efficient forecast data is ensured, realistic cost titles are considered in proposed models, and also the minimum total supply chain cost values under demand, lead time and expediting cost pattern changes are presented and examined in detail. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Supply chain management; Multi-echelon inventory management; Stochastic cost model; Neural networks; Neuro-fuzzy approximation; OPTIMAL POLICIES; DEMAND UNCERTAINTY; SYSTEM; MODEL; APPROXIMATIONS; NETWORKS; Computer Science; Engineering; Operations Research & Management Science